(untitled) (The Pretoria Student Law Review, 2023)
This article explores the relationship between human rights anddevelopment and the emergence of a Rights-Based Approach toDevelopment (RBAD). It will give a RBAD more consideration in order tocontribute to the conceptual direction of academic discourse, andperhaps even the political direction by proposing solutions to Africa’ssocio-economic problems, especially in South Africa, which is facingmany developmental challenges. Human rights and development havelong been understood as separate terms that were incompatible.Historically, development was only perceived for its role in promotionof economic growth and prosperity of particular countries without anyconsideration for human development and well-being. However, humanrights and development cannot be understood separately. Developmentand human rights share the same goal, which is to promote the dignityand worth of a human person by creating an environment where peoplecan achieve their full potential. Following the adoption of the UNCharter in 1945, development became a key issue for the United Nationsand, for the first time, for the international community. Humandevelopment is now central to the realisation of human rights. Aftermany years of debating development and human rights, it was agreedthat human rights standards and principles do indeed recognise the linkbetween human rights and development. In the 1990s, a RBAD emerged,transforming the global development order and affirming thisrelationship.